Look on the bright side ebook - Higgins, Kristan (2024)
From the author of Pack Up the Moon comes a funny, romantic, and deeply moving novel about the unexpected rewards that come from life’s detours. Lark Smith has always had a plan for her life: find a fantastic guy, create a marriage as blissful as her parents’, pop out a couple of kids and build a rewarding career as an oncologist. Things aren’t going so well. For one, the guy didn’t work out. Theoretically, she’d love to find someone else, but it hasn’t happened. Two, she’s just been transferred out of oncology for being too emotional. (Is it her fault she’s a weeper?) Three, her parents just split up. Deviating from the plan was…well, not in the plan. A potential solution comes from the foul-tempered and renowned surgeon Lorenzo Santini (aka Dr. Satan). He needs a date this summer for his sister’s wedding. His ancient Noni wants to see him settled. In exchange, he could make a few introductions and maybe get Lark back into the field of her choice. As a sucker for old people and fake relationships, Lark agrees. Teeny problem—she instantly falls for his big, warm family. Especially his estranged brother. Meanwhile, Lark’s mom has moved in with Lark’s colorful landlady, Joy, and an unlikely friendship blossoms. The three women have a long summer and a big beautiful house on the ocean to figure out what’s next…and quite possibly learn that the best things in life aren’t planned at all.